1983
DOI: 10.1159/000166717
|View full text |Cite
|
Sign up to set email alerts
|

Hyporeninemic Hypoaldosteronism, Sodium Wasting and Mineralocorticoid-Resistant Hyperkalemia in Two Patients with Obstructive Uropathy

Abstract: The renin-aldosterone system and tubular responsiveness to exogenous mineralocorticoid administration was evaluated in 2 hyperkalemic patients with obstructive uropathy. Both patients manifested marked renal sodium wasting and a modest inability to lower urine pH despite systemic acidosis. None of the abnormalities was corrected with supraphysiologic doses of mineralocorticoid. In addition, plasma renin and aldosterone levels were inappropriately low. Thus, both hypoaldosteronism and renal tubular resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Therefore, in our case nephropathy can also contribute to severe hyperkalemia together with AD. Patients with chronic renal insufficiency frequently have an impaired kaliuretic response to exogenous mineralocorticoid administration, suggesting that enhanced distal chloride reabsorption may account for many of the findings of hyporeninemic hypoaldosteronism (11). Rapid increases in K + concentrations may potentiate the cardiotoxic effects of hyperkalemia, whereas if hyperkalemia develops slowly (e.g., chronic renal failure), cardiac manifestations may be attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in our case nephropathy can also contribute to severe hyperkalemia together with AD. Patients with chronic renal insufficiency frequently have an impaired kaliuretic response to exogenous mineralocorticoid administration, suggesting that enhanced distal chloride reabsorption may account for many of the findings of hyporeninemic hypoaldosteronism (11). Rapid increases in K + concentrations may potentiate the cardiotoxic effects of hyperkalemia, whereas if hyperkalemia develops slowly (e.g., chronic renal failure), cardiac manifestations may be attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive nephropathy has been associated with several types of dRTA and hyperkalemia [11][12][13][14][15][16], Batlle et al [3] studied 13 patients with obstructive uropathy, hyperkalemia, and dRTA. Three types of renal tubular dysfunction were identified: selective hvpoaldosteronism, a 'voltage-dependent' acidification defect, and 3 patients with a com bination of both, while Pelleya et al [15] reported 2 adults, and Rodriquez-Soriano et al [16] have described 6 infants with salt-wasting and mineralocorticoid-resistant hyperkalemia, i.e., aldosterone resistance (pseudohy poaldosteronism type I). More recently Alon et al [17] have reported 3 neonates with unilateral kidney disease who had incomplete end-organ resistance to aldosterone (dRTA type 4, subtype 5) [5].…”
Section: ]mentioning
confidence: 99%
“… HA.14 reports, 33 patients, plus an unreported case of our own 8–21 . Twenty‐two of these patients had associated renal impairment and two also had PHA.…”
mentioning
confidence: 94%
“…Renal impairment and hyperkalemia. Ten reports, 43 patients plus two unreported cases of our own 5,9,11,13,14,16–19,40 . Of the 45 patients, 22 had been included in the HA data.…”
mentioning
confidence: 99%
See 1 more Smart Citation